2020
DOI: 10.3329/bjo.v23i2.45165
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic characteristics of the patients of Tonsillitis attended in OPD of a district level Hospital

Abstract: Aim: To find out the tonsillitis patients and also find out its sociodemographic characteristics in district level of Bangladesh. Method: This was a prospective cross sectional study, which was carried in out patients of tonsillitis attended in OPD of 250 Bedded General Hospital, Gopalganj. All the patients of acute tonsillitis, chronic tonsillitis and adenoid hypertrophy were selected from OPD irrespective of sex during the period of July 2015 to June 2016. Age ranges from 0-90 years and person resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Mahfuz reported similar results that out of 2176 chronic tonsillitis patients, more than half, accounting for 55.97%, were aged 0-15 years [4]. Another study in Jambi reported that the peak incidence of chronic tonsillitis occurred at the age of 5-14 years, with a percentage of 50% [18].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Mahfuz reported similar results that out of 2176 chronic tonsillitis patients, more than half, accounting for 55.97%, were aged 0-15 years [4]. Another study in Jambi reported that the peak incidence of chronic tonsillitis occurred at the age of 5-14 years, with a percentage of 50% [18].…”
Section: Discussionmentioning
confidence: 78%
“…According to Mahfuz et al, there is a 50% increased risk of respiratory tract infection in children. This includes tonsillitis with Vitamin D levels <70 nmol/L and a 70% increase in levels below 50 nmol/L [4]. Meanwhile, Safak et al reported that VEGF was higher in children with serum Vitamin D <20 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampel jenis kelamin perempuan yang menderita tonsilitis kronik lebih banyak daripada jenis kelamin laki-laki dengan persentase sebesar 63.3%. Hal ini sejalan dengan penelitian yang dilakukan di Bangladesh tahun 2015-2016 yang menyatakan bahwa jenis kelamin perempuan lebih banyak daripada laki-laki dengan perbandingan 1.2:1 (Mahfuz & Kabir, 2017). Selain itu, penelitian yang dilakukan di RSUD Dr. Rasidin Padang tahun 2018 juga memiliki hasil yang serupa dimana jenis kelamin perempuan memiliki persentase lebih tinggi daripada laki-laki (51.4%) (Tamara et al, 2020).…”
Section: Distribusi Karakteristik Subjek Penelitianunclassified
“…Jika dilihat dari segi usia, penderita tonsilitis kronik paling banyak berada di rentang usia 5-15 tahun dengan jumlah 14 orang (46.7%). Hal ini sejalan dengan penelitian di Bangladesh tahun 2015-2016 bahwa penderita tonsilitis paling banyak terjadi pada rentang usia 0-15 tahun sebanyak 1218 orang (55.97%) (Mahfuz & Kabir, 2017). Selain itu pada penelitian lainnya di India tahun 2004-2007, penderita tonsilitis kronik juga paling banyak berada di rentang usia 1-10 tahun dengan jumlah 55 orang (36%) (Raju & Selvam, 2012).…”
Section: Distribusi Karakteristik Subjek Penelitianunclassified